DANCE IN THE PERSPECTIVE OF SPORTS EDUCATION TEACHERS (Fiep Bulletin - online, 2011)
In this present research work we identified the perceptions about Dance in a school context of 38 teachers, participants in the World Congess – Active Lifestyles: The Impact of Education and Sport, organized by AISEP (Association Internationale des Écoles Superieures d'Education Physique - International Association fo Physical Education in Higher Education) in Lisbon, in 2005. This work is based on the implicit theories model of the Processes of Thought and Action of professors Clark and Peterson (1986), in which an inquiry form of semi open questions was applied to the teachers, mainly belonging to the Physical Education area, of different European and non-European countries. The analysis of the results reveal there are no significant differences between gender, age and the education levels of the participant teachers, and the self-perception on their competence of dance teaching and including it in the curricular plan. The study also reveals different perceptions about the importance of teaching dance in school environments.
Keywords: Dance; Thought; Physical Education Teachers